Feasibility of Buckwheat Cultivation in Souphanouvong University Campus - Briatia, Xoxiong; Sithivohanh2 , Insavai; Park, Cheol Ho (Souphanouvong University Journal Multidisciplinary Research and Development, 2018)
The objective of this experiment was to study the feasibility of buckwheat cultivation in Souphanouvong University campus by observation for the plant growth characteristics and seed yield. The experiment was conducted at the research farm of the Faculty of Agriculture and Forest Resource, Souphanouvong University from November to February. The experimental design was CRD (Completely Randomized Design) with 3 replications and 3 treatments (Buckwheat cultivars, Suwon 1, Suwon 2 and KW45) with plot sizes of 1x5 meters and plant density 10x20 centimeters. Results found that the highest seed germination rate and germination vigor rate was revealed in Suwon 2 cultivar and higher than Suwon 1 and KW45, respectively. However, the age of plant flowering 50% (25 days after seeding), seed maturity (42 days after seeding) and seed harvesting (60 days after seeding) of Suwon 1 was non-significantly difference compared to Suwon 2, whereas, KW45 showed at 30, 45 and 71 days after seeding, respectively. On the other hand, plant growth characteristics of Suwon 1 cultivar showed higher and bigger than that Suwon 2 and KW45 cultivar. While, KW45 showed more number of flower and seed per plant than Suwon 1 and Suwon 2, but lower of full-seed. Likewise, the plant flowering and seed setting rate of Suwon 1 and Suwon 2 were non-significance different, but Suwon 1 showed full-seed lower than Suwon 2. Similarly, Suwon 1 and Suwon 2 showed seed weight of 0.04 g/seed, 32 g/1000 seeds, total seed weight 1.29 g and 1.28 g/plant, respectively, with productivity of 137.60 and 136.53 kg/rai. Whereas, KW45 cultivar showed seed weight of 0.03 g/seed, 19.66 g/1000 seeds and productivity of 68.27 kg/rai, respectively. Conclusion that three cultivars of buckwheat species were showed plant growth characteristics and seed yield in the level of medium to high, so, its possible to promote and extend into local areas for cultivation after main crops harvested. However, this kinds of experiment stilled need more to confirm and extends into the local areas of the eight northern provinces of Laos in further.